In vitro measurement volume of the neonate thyroid gland - Atyaf Mohammed Ali1 , Anas Hamed Musleh1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Measurement and replacement fluid methods to estimate the thyroid gland volume. Because there is wideranging of variation in the volume of the thyroid gland in healthy individuals of different geographicallocation, ages, gender, and races.Objectives: To estimate normal neonate thyroid gland volume it can throwlight to help clinicians deal better with the gland during neonatal age besides providing native standarddata. Period: From Sept 13, 2018, to Mar 22, 2019. Material & Methods: Total of 48 subjects wereincluded, 24 male and 24 female. The neonate thyroid gland collected and inspected grossly and taken allmeasurements, then use these measurements for finding volume thyroid gland. Also, the volumeis taken byusing replacement fluid. Results: The mean aggregate thyroid gland volume of measures method for malesubjectsstudy was 250.53 ± 4.37mm3, while a female was 246.31 ± 3.42 mm3. The mean volume thyroidgland of replacement fluid method for male subjects study was 295.71 ± 4.41mm3, while the female was291.43 ± 4.04. The mean thyroid volume of the male is expressively larger than female in both methods butstatically non-significant variation. The difference between both ways statistically highly significant (p<0.01). Conclusion: according to results that achieved by two methods, we should use another correctionfactor, higher than 0.749, until getting the nearest value to replacement fluid. Working out different ages toestablish average data.